Deep sternal osteomyelitis: An algorithm for reconstruction based on wound width. Issue 5 (October 2013) - Weinand, Christian; Xu, Weiguo; Perbix, Walter; Theodorou, Panagiotis; Lefering, Rolf; Spilker, Gerald
Abstract Patients with sternum osteomyelitis are transferred to plastic surgery departments for wound coverage. Several options of flap coverage are known; however, various wound diameters need different flaps. In a retrospective study, 135 patients from 2006–2010 with deep sternal wound infections were evaluated. From 2006–2009 various flaps were used for wound coverage, as described in published reports. In 2010 a developed algorithm was used for defect coverage based on wound width using pectoralis muscle flaps or the latissimus dorsi muscle flap. Two groups of patients were analyzed, from 2006–2009 and 2010, and in a matched pair analysis patients with small wound width less than 6 cm, medium wounds widths between 6–12 cm, and large wound width larger than 12 cm. End-point was wound dehiscence larger than 1 cm. Statistical analysis was done by Mann Whitney U-test using the SPSS program. Forty-eight patients were included in the match from a total of 130 study patients. Statistical analysis did not show significant difference in patient population of the two groups. In the group with wound sizes less than 6 cm a significant difference was found when using the algorithm. In the other groups no statistically significant difference was seen; however lesser numbers in wound dehiscence were found. In addition, a significantly lesser length of stay was found in the ICU and length of the hospital stay for all groups treated according to the algorithm. A reduction of costs may be achieved when using the algorithm based on wound size.